Sudden Infant Death Syndrome: Implications of Altered Physiological Control During Sleep - S.C. Horne, Rosemary; B. Witcombe, Nicole; R. Yiallourou, Stephanie; L. Richardson, Heidi (Current Pediatric Reviews, 2010)
A failure of cardiorespiratory control mechanisms, together with an impaired arousal from sleep response, is believed to play an important role in the final event of the Sudden Infant Death Syndrome (SIDS). The ‘Triple Risk Model’ describes SIDS as an event that results from the intersection of three overlapping factors: [1] a vulnerable infant, [2] a critical developmental period in homeostatic control, and [3] an exogenous stressor. In an attempt to understand how the Triple Risk Hypothesis is related to infant cardiorespiratory physiology many researchers have examined how the known risk factors for SIDS alter infant physiology and arousal particularly during sleep. This review discusses the association between the three components of the Triple Risk Hypothesis, the major risk factors for SIDS (prone sleeping and maternal smoking), together with three “protective” factors (breastfeeding, pacifiers and swaddling), and cardiovascular control and arousability from sleep in infants, and discusses their potential involvement in SIDS.
Keywords: arousal